Therapeutic strategy of third-generation autologous chondrocyte implantation for osteoarthritis - Kuroda, Tomoya (Informa Healthcare, 2011)
BACKGROUND: Autologous chondrocyte implantation (ACI) is considered a promising choice for the treatment of cartilage defects. However, the application of ACI to osteoarthritic patients is, in general, contraindicated. The purpose of this study is to evaluate the efficiency of three-dimensionallystructured ACI (3D-ACI; CaReS) in a rat model of knee osteoarthritis (OA). METHODS: OA-like degenerative changes in the articular cartilage were created by transecting the anterior cruciate ligament (ACLT) in athymic nude rats. Two weeks later, CaReS was transplanted at the cartilage injury sites created by micro-drilling in the patella groove (Chondrocyte-implanted (CI) group: CaReS collagen with human chondrocytes; Collagen group: CaReS collagen without cells; and Sham group: sham operation; n = 15/group). RESULTS: Reverse Transcription Polymerase Chain Reaction (RT-PCR) analysis demonstrated the expression of human-specific type 2 collagen and Sry-type high-mobility-group box 9 (SOX9) in the CI group—not in the other groups—throughout the study period. Double immunohistochemistry for human-specific type 2 collagen and human leukocyte antigen-abacavir (HLA-ABC) at week 4 showed positive staining in the CI group only. Macroscopic assessment showed better repair at the cartilage defect sites in the CI group, compared to the other groups. Histological assessment with toluidine blue staining showed that the thickness of the articular cartilage and semi-quantitative histological scores were higher in the CI group than in the other groups up to week 20. CONCLUSIONS: We demonstrate, for the first time, that 3D-ACI is effective in repairing cartilage defects in a rat model of ACLT-induced OA.